Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas V SD Swasta GKPS 1 Pematangsiantar - Elisabeth Ronauli Simanullang; Esti Sirait; Yanti Arasi Sidabutar (Politeknik Kampar, 2024)
The purpose of this research is to determine the effect of the problem based learning model on the science learning outcomes of fifth grade students at GKPS 1 Pematangsiantar Private Elementary School. This research is a pre-experimental research using a one group pretest-posttest design, the sample of this research is 25 people. The data collection technique is a test. By carrying out the pretest, they got an average result of 59, then they were given treatment after being given treatment using the problem based learning model so they got a posttest score with an average score of 86.6. With the scores obtained, the posttest scores have a higher average than the pretest. After carrying out the posttest, the researcher carried out the n-gain test and got an n-gain score of 0.6848 which was categorized as medium and the hypothesis test got a value of 21,315. The results of the t test obtained t = 21.315 with a significance level of 0.000. because the significant probability is much smaller than 0.05, namely 0.000 and tcount = 21,315 > ttable = 1,710, then HO is rejected and Ha is accepted. This shows that it means that there is an influence of the problem based learning model on the science learning outcomes of class V students at GKPS 1 Pematangsiantar Private Elementary School for the 2024/2025 academic year.